Rethinking British Diaspora: The Question Of Home And Identity Construction In Caryl Phillips’ In The Falling Snow (2009) (مجلة الواحات للبحوث والدراسات, 2020)
In the realm of diaspora, a lot has been said concerning identity construction. Within the diaspora studies, the issue of identity has been a topic of debate due to the imperious acknowledgment of an earlier ‘elsewhere’ and the degree of attachment to the erstwhile culture. Many questions have been put forward to reach the very meaning of identity when it is foregrounded and contextualized within the struggles of universality and essentialism.  Among the raised questions the one which leads to the search for the sense of identity and structure of being when the local and the international are juxtaposed. These do not seem to be the only questions. There are, in fact, other questions which deal with the proclivity for honoring ‘home’that would make of the Diasporic person a perpetual changing person called the “chameleon”, and deal with the possibility of orchestrating a single and homogenous opus apart from colliding voices. Apart from the calls for breaking off with the national ties and cultural artifacts that characterized the diaspora accounts, at any given point, diaspora communities seem to inherit certain cultural institutions and traditions that are definitive for their existence. Caryl Phillips’ In the Falling Snow (2009) questions the different momentums that hinge on diaspora populace and their endeavor while constructing their identities, through offering a critique to the issues of integration, assimilation, acculturation and adjustment that keep reiterating diaspora communities. One is supposed  to check how  does home operate and serve as an analytical category of identity, how the conundrums of home could open up inscrutable chasms between the international and the local , and the possibility of finding the self, though fortuitously, thinking about the different spectrums of inclusion/exclusion and the assertion of rights within the recipient land. Keywords-British Diaspora, Home, Identity, International, Local